Operators' guide to trace elements in anaerobic digestion. (2018) - Roussel, Jimmy; Fermoso, Fernando G; Collins, Gavin; Van Hullebusch, Eric; Esposito, Giovanni; Mucha, Ana Paula
No abstract available